Filter Air Sederhana untuk Kebutuhan Air Bersih Warga Jalan Sei Wain RT 36, Kelurahan Karang Joang, Kecamatan Balikpapan Utara - Manta, Faisal; Suanggana, Doddy; Dwi H, Hadhimas; Haliq, Ridwan; Sa’adiyah, Devy Setiorini; Rahmany, Rijal Surya; Batubara, Yongki Christandi; Sujana, I Made Ivan Wiyarta Cakra; Zufadli, Muhammad Syahmi; Hidayat, Dinda Khoirunnisa; Marshantya, Defiana; Syaharani, Destyana Putri; Stofani, Dhio; Rajagukguk, Grendy Ary Krishna; Yuike, Ariesta; Saputra, Ferry Adi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Kalimantan Institute of Technology (ITK) 2024 service activities will be held on Jl. Sei Wain RT. 36 Kel. Karang Joang, Kec. Balikpapan Utara, Balikpapan City, East Kalimantan was compiled based on the partner's problem, namely the availability of clean water in the area. The use of unclean water has an impact on the health quality of residents of RT 36, such as irritation and itching on residents' skin. Based on these problems, the ITK community service team decided to create appropriate technology, is a simple water filter that can improve the quality of clean water for residents of RT 36. Community service activities begin with field reviews, partner coordination, mapping of problems and solutions such as water quality tests used by partners, literature studies on the appropriate technology applied, water filter design and material purchases, filter manufacturing on site with partners, water quality testing of filtered results, measuring the impact of the application of appropriate technology on partners, closing the event at the partner's location. Based on a visual inspection of the filtered groundwater of RT 36 residents, it is known that the color of the water has become clearer, reducing the smell of iron and dissolved sediment. The results of the questionnaire stated that 80% agreed that the application of water filters provided benefits and improved water quality, but 35% of residents had difficulty in assembling and making the water filters.